SUSTAINABLE TRANSFORMATION OF THE ENERGY SYSTEM IN IRAQ AND ITS ROLE IN SUSTAINABLE DEVELOPMENT (World Economics and Finance Bulletin, 2022)
Energy is an integral part of many of these challenges. The region depends heavily on oil and natural gas. Yet the region is a key energy producer, many countries in the Middle East and North Africa struggle to meet the increasing domestic need for energy. Switching to energy systems on the basis of renewable energy promises to meet this need. The switching also reduces greenhouse gas emissions under the Paris Agreement. Additionally, renewable energy use has the potential of increasing economic growth and employment reducing financial constraints.